Data analytics using Spark and Hadoop : learn how to integrate Spark and Hadoop in a series of hands-on labs - Maniyam, Sujee (O'Reilly, 2016)
"Hadoop and Spark are the stars of the Big Data world. This course covers the basics of Spark and how to use Spark and Hadoop together for big data analytics. Designed for developers, architects, and data analysts with a fundamental understanding of Hadoop, it begins with an overview of how Hadoop and Spark are used in today's big data ecosystem before moving into hands-on labs that demonstrate Spark and Spark-Hadoop integration. You'll learn about the Spark shell, RDDs, and DataFrames; how to query data in Hadoop Hive Tables from Spark; and how to develop Spark applications and run them on YARN."--Resource description page.